Mitigating unfairness problem in WLANs caused by asymmetric co-channel interference. (2018) - Mahmud, Md. Sultan; Uddin, Md. Forkan
The impact of co-channel interference is investigated in IEEE 802.11-based wireless local area networks (WLANs) via simulation and it is found that the throughput unfairness among the users is severe due to asymmetric co-channel interference among the users. A centralised algorithm is proposed based on an analytical formulation to mitigate the throughput unfairness problem in WLANs by configuring the minimum contention window (CW) of the nodes. A heuristic is developed based on the results of the centralised algorithm to configure the minimum CW of the nodes and then a simple and practical distributed algorithm is proposed to mitigate the throughput unfairness problem in WLANs. The performance of the proposed algorithms is evaluated by simulation and found to be very effective to mitigate the throughput unfairness problem in WLANs.